Isolation, identification and antagonistic activity evaluation of actinomycetes in barks of nine trees - Wang, Dong-sheng; Ren, Hai-ke; Erihemu, Erihemu; Zheng, Zhi-yi (Archives of Biological Sciences, 2017)
Actinomycetes are important producers of novel bioactive compounds. New sources need to be explored for isolating previously unknown bioactive compound-producing actinomycetes. Here we evaluated the potential of bark as a natural source of novel bioactive actinomycete species. Bark samples were collected from nine tree species at different elevations (1600-3400 m a.s.l.) on Qin Mountain, Shaanxi Province, China. Actinomycetes were cultivated, enumerated and isolated using serial dilution and spread-plate techniques. The antimicrobial activity of actinomycete isolates was analyzed using an agar block method against 15 typical bacterial and fungal species and plant pathogens. The dominant isolates were identified by 16S rRNA-based sequence analysis. Results showed that actinomycete counts in bark samples of Quercus liaotungensis Koidz. was the highest among all trees species tested. The numbers of actinomycete species in bark samples were highest in Q. aliena var. acutiserrata and Spiraea alpina Pall. Antagonistic activity was detected in approximately 54% of the actinomycete isolates. Of these, 20 isolates (25%) showed broad-spectrum antagonistic activity against ≥5 of the microorganisms tested. In conclusion, the bark on coniferous and broadleaf trees possesses a high diversity of actinomycetes and serves as a natural source of bioactive compound-producing actinomycetes. https://doi.org/10.2298/ABS160429109W Received: April 29, 2016; Revised: May 30, 2016; Accepted: June 3, 2016; Published online: November 4, 2016 How to cite this article: Wang D, Ren H, Erihemu, Zheng Z. Isolation, identification and antagonistic activity evaluation of actinomycetes in barks of nine trees. Arch Biol Sci. 2017;69(2):345-51.